Avaliação dos efeitos anti-inflamatórios do produto do plasmídeo de expressão eucariótica codificante de scFv anti-IL-1β carreado por uma linhagem invasiva de Lactococcus lactis na doença de Crohn experimental induzida por TNBS - Ramos, Anderson dos Santos (2020)
Crohn's disease is an inflammatory bowel disease characterized by exacerbated chronic inflammation that results in severe damage to the intestine. The treatment of this disease aims to reduce inflammation and promote healing of the mucosa. IL-1β is a pro-inflammatory cytokine that triggers intestinal inflammation and participates in the pathogenesis of the disease, becoming a candidate for a therapeutic approach. However, the lack of success of IL-1β inhibitors in the treatment of this disease may be associated with the intravenous administration route that causes systemic inhibition of this cytokine and side effects. To overcome these limitations, the local release of biopharmaceuticals can change the current scenario, restricting therapy at the inflammatory site. The development of Lactococcus lactis strains capable of providing a eukaryotic expression vector that encodes a single-chain variable fragment (scFv) of the antibody represent a promising strategy for the development of an effective therapy, capable of guaranteeing the expression of the antibody directly in the mucosa tract inflamed intestinal tract. Thus, the objective of this work was to evaluate the anti-inflammatory effects of L. lactis (FnBPA) carrying the pValac plasmid that encoding anti-IL-1β scFv in an experimental model of chemically TNBS induced Crohn's disease by. For that, female BALB/c mice were submitted to experimental colitis induced by TNBS for four weeks. The L. lactis culture was administered orally in the last 5 days of the experimental protocol. The day after the last treatment day, the animals were euthanized and the macroscopic, histopathological and histochemical parameters were evaluated. An improvement in the macroscopic parameters of the disease was observed in the group treated with L. lactis FnBPA + (pValac::anti-IL-1β) in relation to the other groups submitted to induced colitis. In the histopathological analysis, the beneficial effect of the treatment was better in the proximal region of the colon, with a reduction in the score of histological damage, due to the reduction of the inflammatory infiltrate and maintenance of the mucous layer. However, treatment with L. lactis FnBPA + (pValac::anti-IL-1β) reduced mucin-producing cells, indicating a detrimental effect of IL-β inhibition in the model. In summary, the results suggest the benefits of L. lactis FnBPA + (pValac::anti-IL-1β) in reducing some colitis parameters, but the side effects on mucins production reinforce the pleiotropic action of IL-1β in the experimental model of disease of Cronh.